DEVELOPMENT OF THE MECHANISM OF FORMATION OF THE REGIONAL SYSTEM OF ENERGY SAVING MANAGEMENT ON THE BASIS OF EXPERIENCE OF THE COUNTRIES OF THE EUROPEAN UNION - Klymchuk, M.M.; Klymchuk, S.A. (The actual problems of regional economy development, 2020)
The article examines the theoretical aspects of development and implementation of energy efficiency policy of the regions, highlights the main directions of its implementation. The main tools for stimulating energy saving in the EU countries are considered. The current international projects for the development of regional energy efficiency policy and support for enterprises implementing energy saving measures in the European Union are analyzed. The constituent elements of the project evaluation system according to the criteria are formed: development of smart-technology, introduction of financial instruments, interregional cooperation, strategies of intellectual specialization. In order to provide financial resources for energy saving and energy efficiency projects, we have provided proposals for the use of municipal bonds and compensatory technology "Tax Increment Financing". Based on the results of studying global trends in energy management at the regional level, we proposed a mechanism for forming a regional energy management system, as a set of principles, goals, objectives, functions, entities, process, taking into account existing needs and opportunities for energy saving measures. Within the framework of introduction of the mechanism of formation of the regional system of management of energy saving the characteristic of the purposes (economic; social; ecological) is given; tasks (organizational; institutional; infrastructural; investment; innovation; socio-economic; environmental; information); principles (rational use of resources; scientific substantiation of management; public-private partnership; adaptation and mobility); entities, functions and management tools.